Effect of Incentives, Career Development and Employment Conflict on Employee Achievement at PT. Plasindo Works - Kristina Tantri; Jerry Febriant; Stif Wie Son; Fajar Rezeki Ananda Lubis (Universitas Pamulang, 2022)
The purpose of this study was to determine and analyze the effect of incentives, career development and work conflict on employee performance at PT. Karya Plasindo so that the company can improve and improve the work performance of its employees. The research methodology used is explanatory research. The total population is 141 employees while the sample obtained by the Slovin formula is 105 people. The data processing technique used multiple linear regression analysis. The results of this test show that either partially or simultaneously, career development and work conflict have a positive and significant impact on employee performance at PT. Plasindo's work. The magnitude of the influence of the variable is 40.4% which is influenced by other factors.